2015
DOI: 10.1183/13993003.00779-2015
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and inflammatory characteristics of the European U-BIOPRED adult severe asthma cohort

Abstract: U-BIOPRED is a European Union consortium of 20 academic institutions, 11 pharmaceutical companies and six patient organisations with the objective of improving the understanding of asthma disease mechanisms using a systems biology approach.This cross-sectional assessment of adults with severe asthma, mild/moderate asthma and healthy controls from 11 European countries consisted of analyses of patient-reported outcomes, lung function, blood and airway inflammatory measurements.Patients with severe asthma (nonsm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
387
3
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 481 publications
(453 citation statements)
references
References 37 publications
16
387
3
15
Order By: Relevance
“…Phenotypes may be based on the presence and level of inflammation, which may be termed inflammatory phenotypes [16], or based on a combination of clinical characteristics, physiological, and inflammatory markers, which may be termed clinical phenotypes [1722]. …”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…Phenotypes may be based on the presence and level of inflammation, which may be termed inflammatory phenotypes [16], or based on a combination of clinical characteristics, physiological, and inflammatory markers, which may be termed clinical phenotypes [1722]. …”
Section: Systematic Assessment Of Severe Asthmamentioning
confidence: 99%
“…The recent European U-BIOPRED adult severe asthma cohort, including more than 400 severe asthmatic patients, has shown that the majority of severe asthmatics had sputum eosinophils > 3%. Interestingly, those with a current or a past history of smoking did not have less sputum eosinophils, clearly indicating that smoking history in asthmatics does not preclude the presence of eosinophilic inflammation 59 . In the same study, there is clearly no link between asthma severity and sputum neutrophil counts.…”
Section: Barcelona Respiratory Networkmentioning
confidence: 95%
“…The EU-funded Unbiased Biomarkers for the Prediction of Respiratory Disease Outcomes (U-BIOPRED) project has just published details of their paediatric and adult severe asthma cohorts 31,32 . This cross-sectional assessment of adults with severe asthma, mild/ moderate asthma, and healthy controls from 11 European countries showed that patients with severe asthma had more symptoms and exacerbations (2.5 exacerbations versus 0.4 in the preceding 12 months) compared to patients with mild/moderate disease, with worse quality of life and higher levels of anxiety and depression.…”
Section: Phenotyping Based On Clustering Of Clinical-physiological Datamentioning
confidence: 99%